A study on prevalence of anaemia among reproductive age group females attending urban health center of Anakaputhur area of Kancheepuram district - Aljin, V.; Umadevi, R.; Hariharan, S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Anaemia, a major public health threat and real challenge for the health care professionals, for the past several decades. The burden of anaemia is high especially among females of reproductive age group, who are a vulnerable population undergoing pregnancy and child birth at this stage of their life. Thus this study was aimed to find the prevalence of anaemia among the reproductive age group females attending an urban health center in Tamil Nadu. Methods: A hospital based, cross sectional study was conducted among reproductive age group females, attending Urban Health Training Center. 292 patients, who gave written consent were included and interviewed using a questionnaire followed by haemoglobin assessment with venous blood sample. Results: The mean age of the study participants were 34.6±12.4 years with 9.6% uneducated and 7.2% graduate females. 26% gave history of symptoms of anaemia and prevalence of anaemia was reported to be 42.12% with 24.31%, 12.32% and 5.5% of mild anaemia, moderate anaemia and severe anaemia, respectively. Conclusions: With immense efforts, prevalence of anaemia is still high, in this study. Prevention and treatment of anaemia in women is much essential at this point and therefore programmes and policies should be implemented based on the needs of the community and health education should be imparted with respect to measures that can prevent and helps in early diagnosis of anaemia.